Framework for action on maximising civil society's contribution to development and democracy 2004 - 2008 (Commonwealth Foundation LondonGB, 2004)
Identifies actions that need to be taken not only by civil society organisations but also by governments, donors and Commonwealth agencies.
Keywords: CIVIL SOCIETY